2019
DOI: 10.1093/pm/pny313
|View full text |Cite
|
Sign up to set email alerts
|

Level of Low Back Pain–Related Disability Is Associated with Risk of Subsequent Falls in an Older Population: Locomotive Syndrome and Health Outcomes in Aizu Cohort Study (LOHAS)

Abstract: Objectives To examine the longitudinal association between baseline disability due to low back pain (LBP) and future risk of falls, particularly significant falls requiring treatment, in a community-dwelling older population. Methods This was a prospective population-based cohort study using data from the Locomotive Syndrome and Health Outcomes in Aizu Cohort Study (LOHAS; 2008–2010). A total of 2,738 residents aged ≥60 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Previous studies have reported that chronic LBP was associated with decreased mobility function in older populations [29,38]. The results of the current study showed that severe LS was associated with LBP among older women who were scheduled to undergo surgery because of degenerative lower extremity diseases.…”
Section: Plos Onesupporting
confidence: 55%
“…Previous studies have reported that chronic LBP was associated with decreased mobility function in older populations [29,38]. The results of the current study showed that severe LS was associated with LBP among older women who were scheduled to undergo surgery because of degenerative lower extremity diseases.…”
Section: Plos Onesupporting
confidence: 55%
“…Although our results did not theoretically discriminate among the 3 factors completely without cross-loading and residual correlations, it would potentially be able to assist clinical physicians in understanding the concept of LS (pain, movement-related difficulty and psycho-social complication) because these factors fundamentally contribute to the concept of LS and are closely linked with each other. Moreover, previous studies also reported relationships between musculoskeletal pain (Hirano et al, 2014;Iizuka et al, 2015;Imagama et al, 2017;Kimachi et al, 2019), movement-related difficulty or functional decline (Akai et al, 2016;Iwaya et al, 2017;Izawa et al, 2019;Muramoto et al, 2012;Yoshimura et al, 2011), and psycho-social complication (Ikemoto et al, 2016;Nakamura et al, 2017aNakamura et al, , 2017bMaruya et al, 2018) and LS. Thus, it seems reasonable to discriminate among these 3 dimensions when assessing LS during clinical practice.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies have estimated the severity levels of disability using WHODAS 2.0 (either 12-or 36-item version), following two general approaches. First, using the ICF-recommended classification, a population is classified as: no disability [0-4], mild disability [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], moderate disability , severe disability , and extreme disability [96-100]. Second, using some multivariate statistical method, individuals are classified according to the association pattern observed among the items of WHODAS 2.0.…”
Section: Comparison With Findings From Previous Studiesmentioning
confidence: 99%
“…Burden imposed by disability in old age is one of the major challenges faced by healthcare systems worldwide not only in high-income countries (HICs) but also in low-and middle-income countries (LMICs) (3). Disability can occur simultaneously with some geriatric syndromes (falls, frailty, cognitive impairment) (4,5) and chronic conditions (hypertension, myocardial infarction, arthritis, diabetes, stroke) (6,7) and is a major risk factor for adverse outcomes such as falls (8), hospitalizations (9), and mortality (10).…”
Section: Introductionmentioning
confidence: 99%